Perbandingan Tingkat Perolehan Laba Terhadap Penilaian Kinerja Keuangan Bank Umum Milik Pemerintah Indonesia (Bank Mandiri, Bank BRI Bank BTN) Dengan Menggunakan Rasio Keuangan - Fitria Widyastuti; Budi Wahono; Arini Fitria Mustapita (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
Abstract The aims of this study is to determine the profit rate comparison against financial performance at PT Bank Mandiri, PT Bank Rakyat Indonesia, and PT Bank Tabungan Negara in the 2019 period. The sample used in this study are the financial reports of 2019 period from PT Bank Mandiri, PT Bank Rakyat Indonesia, and PT Bank Tabungan Negara. The research method used is descriptive quantitative, to explain the level of financial performance using the Comparison of Financial Ratios and Discriminant Test analysis tools. The results of the research in the discriminant analysis, obtained a significance value above 0.05 so that the results of the study showed that there were differences in the data studied between these three banks. The difference in the level of profit and financial performance between the three banks was obtained by the best ranking by Bank BRI with good criteria, followed by Bank Mandiri with good criteria, then Bank BTN with poor criteria. Keywords: Profit Rate Comparison, Financial Performance, Financial Reports